Sistem Pendukung Keputusan Penentuan Kenaikan Kelas Santri Menggunakan Metode TOPSIS - Alma Arofah; Respitawulan (Jurnal Riset Matematika, 2022)
Abstract. TOPSIS is one of the methods contained in the Multi Criteria Decision Making (MCDM). In general, this method works based on criteria which are the determining factors for a case study by assessing the weight of each criterion. The purpose of this study was to find the priority value of a case of determining the class increase of students at the Al-Falah Dago Islamic Boarding School. The TOPSIS method can make it easier for Islamic boarding schools to determine whether students will go to class or not go to class objectively with predetermined criteria. In the process of determining the class increase of the students of the Al-Falah Dago Islamic Boarding School, there are 42 alternatives with 6 criteria being assessed: the average value of imtihan 1, the average value of imtihan 2, attendance, practice values, discipline values and moral values. The results of this study indicate that the results obtained from the determination of grade promotion from 42 alternatives resulted in recommendations for 27 students to go to class and as many as 15 students not to go to class. Abstrak. TOPSIS merupakan salah satu metode yang terdapat pada Multi Criteria Decision Making (MCDM). Secara umum metode ini bekerja berdasarkan kriteria yang merupakan faktor penentu bagi suatu studi kasus dengan menilai bobot dari setiap kriteria. Tujuan dari penelitian ini adalah mencari nilai prioritas dari sebuah kasus penentuan kenaikan kelas santri Pondok Pesantren Al-Falah Dago. Metode TOPSIS dapat mempermudah pihak pesantren untuk menentukan santri naik kelas atau tidak naik kelas secara objektif dengan kriteria yang sudah ditentukan. Dalam proses penentuan kenaikan kelas santri Pondok Pesantren Al-Falah Dago terdapat 42 alternatif dengan 6 kriteria yang menjadi penilaian: nilai rata-rata imtihan 1, nilai rata-rata imtihan 2, kehadiran, nilai praktik, nilai kedisiplinan dan nilai akhlaq. Hasil penelitian ini menunjukkan bahwa perolehan hasil penentuan kenaikan kelas dari 42 alternatif dihasilkan rekomendasi sebanyak 27 santri naik kelas dan sebanyak 15 santri tidak naik kelas.